Validity of the COPCORD Core Questionnaire as a classification tool for rheumatic diseases (2011)
Rheumatic diseases are vastly underdiagnosed and undertreated, particularly among minorities and those of low socioeconomic status. The WHO-ILAR Community Oriented Program in the Rheumatic Diseases (COPCORD) advocates screening of musculoskeletal complaints in the community. The objective of this study was to evaluate the performance of the COPCORD Core Questionnaire (CCQ) as a diagnostic tool for rheumatic diseases.